2019
DOI: 10.1590/1519-6984.172213
|View full text |Cite
|
Sign up to set email alerts
|

Impact of phosphate solubilizing bacteria on wheat (Triticum aestivum ) in the presence of pesticides

Abstract: Three phosphate solubilizing bacteria were isolated and identified by 16S rRNA sequencing as Pseudomonas putida, Pseudomonas sp and Pseudomonas fulva . The strains were subjected to plant biochemical testing and all the PGPR attributes were checked in the presence of pesticides (chlorpyrifos and pyriproxyfen). The phosphate solubilizing index of strain Ros2 was highest in NBRIP medium i.e 2.23 mm. All the strains showed acidic pH (ranges from 2.5-5) on both medium i.e PVK and NBRIP. Strain Ros2 was highly posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 17 publications
1
7
0
2
Order By: Relevance
“…Similar results have been reported in studies where bacterial strains tested on Pikovskaya agar showed a low solubility index [73][74][75]. The ability of the same bacteria to dissolve phosphates on solid agar and liquid medium differs; some studies have found that the bacteria show a considerably higher phosphate production in liquid medium [76,77]. The low phosphate solubility index may be related to several factors, such as organic acid production or nutrient composition [76,78], but according to the available source, it is not related to origin of the strains.…”
Section: Characterisation Of Actinomycete Strainssupporting
confidence: 84%
“…Similar results have been reported in studies where bacterial strains tested on Pikovskaya agar showed a low solubility index [73][74][75]. The ability of the same bacteria to dissolve phosphates on solid agar and liquid medium differs; some studies have found that the bacteria show a considerably higher phosphate production in liquid medium [76,77]. The low phosphate solubility index may be related to several factors, such as organic acid production or nutrient composition [76,78], but according to the available source, it is not related to origin of the strains.…”
Section: Characterisation Of Actinomycete Strainssupporting
confidence: 84%
“…The siderophores producing bioinocultant treated to mung bean plants protect the plant by reducing the chlorotic lesions on the leaves and also increased the chlorophyll levels under iron-deficient stress [32]. Likewise, increase carotenoids level was observed in siderophores producing strain (Ros2) treated to wheat plants in the presence of pesticide stress [33]. [34] isolated a potential siderophores producing organism from rhizosphere, this bacterium treated to peanut plants showed drastic increase in the seed germination, shoot, root length and also recoded enhanced levels of chlorophyll.…”
Section: Discussionmentioning
confidence: 87%
“…The PSM controls the phytopathogens attack by synthesizing pivotal molecules like siderophores ( Sarr et al, 2020 ), antibiotics ( Raaijmakers and Mazzola, 2012 ), lytic enzymes ( Herrera-Quiterio et al, 2020 ), cyanogenic compounds ( Munir et al, 2019 ), and through induction of systemic resistance (ISR; Audenaert et al, 2002 ). Due to this, the soil PSM improves the growth and grain yield of sorghum by suppressing the damaging impact of biotic stresses.…”
Section: Biotic Stress Alleviation By Psmmentioning
confidence: 99%